Penyintas Bayi Prematur Berat Badan Lahir Amat Sangat Rendah (BBLASR) di RSUD Tipe C: Laporan Kasus: Laporan Kasus - Putri, Dessy Natasha Ade; Naur, Oktaviani Mulianiarti (Cermin Dunia Kedokteran, 2025)
Introduction: Low birth weight is defined by the World Health Organization as a birth weight of less than 2,500 grams, while extremely low birth weight is defined as a birth weight of less than 1,000 grams. Babies with low birth weight are 20 times more likely to experience complications and death compared to babies with normal birth weight. Case: A female infant, gestational age 28–29 weeks, birth weight 800 g, born spontaneously to a G3P1A1 mother with a history of premature rupture of membrane < 18 hours, urinary tract infection, and threatened preterm delivery. The infant cried immediately after birth, AS 7/9, and at 10 minutes appeared to be short of breath with a threat of respiratory distress. CPAP was administered, thermoregulation was performed, and intravenous antibiotics were given. Parenteral nutrition was given starting at 80 mL/kgBW/day and increased gradually. Breast milk was given on the second day starting at 20 mL/kgBW/day every 3 hours via OGT, increased by 10–20 mL/day according to tolerance. Complications during treatment included recurrent temperature instability, brown-colored vomit, and abdominal distension. The infant’s weight dropped to 700 g, and anemia (Hb = 10.6) developed. At 30 days of age, Kangaroo mother care, oral care, and physiotherapy were provided and taught to the parents. At 12 months of corrected age, the infant weighed 7.8 kg and was developing according to age milestones. Discussion: Early feeding plays a crucial role in the care of premature infants because it supports growth and gastrointestinal maturation. Enteral nutrition is better than total parenteral nutrition because it helps prevent problems from IV use, infections, side effects of total parenteral nutrition, and not eating. Conclusion: Prematurity is the leading cause of morbidity and mortality in neonates and children under 5 years of age. Proper management and good nutrition will support optimal growth, improve neurological outcomes, and reduce the incidence of sepsis and the possibility of retinopathy.